Recreational Assessment of Landscapes of Tuva for the Development of Tourism - SAMBUU, Anna (Journal of Environmental Management and Tourism, 2019)
The article considers the recreational assessment of natural landscapes of Tuva, which are one of the priority directions of geographical science, in connection with the General trend of preserving the balance of nature and sustainable development of tourism. Tuva is the youngest region, which became part of Russia in 1944, the Republic has huge tourism potential, combining a unique variety of natural conditions from the picturesque landscapes, the richness of fauna and flora, preserved national traditions and unique monuments of nature and history. On a relatively small area there are almost all natural areas of the Earth: deserts and mountain glaciers, steppes and taiga, tundra and Alpine meadows. The variety of natural conditions of the mountainous territory determined the richness of its flora and fauna. There are 2 nature reserves, 16 nature reserves, 15 natural monuments. The state nature biosphere reserve "UVS Nuur Basin" is a UNESCO World natural heritage site. Featuring a variety of natural conditions and historical and ethnographic features, Tuva is a promising region in terms of tourism. This situation makes it possible to fully meet the growing needs of tourists. Taking into account all factors, tourism in the Republic of Tuva will be put forward as a priority for the development of the national economy. However, in the field of tourism of the Republic there are problems and limitations associated with the current state of tourism infrastructure, etc.